MENINGKATKAN KEMAMPUAN MEMBACA NYARING DENGAN INTONASI YANG TEPAT MELALUI METODE LATIHAN PADA ANAK KESULITAN BELAJAR - Sefrida - - (Jurnal Penelitian Pendidikan Khusus, 2012)
This research background by disability problems faced by children learning to read in elementary grade IV N 01 Limau Manis Padang who do not have the ability to read aloud with proper intonation. This study aims to prove the effectiveness of training methods to improve the ability to read text aloud with intonation appropriate announcement on disability children learn to read. This type of research that researchers use the Single Subject Research (SSR) is a study done in different conditions using ABA design. Thus the hypothesis can be accepted, that an effective training method to improve the ability to read aloud with proper intonation on ability children learn to read.